Benefits of Decision-Support by Likelihood versus Binary Alarm Systems: Does the number of stages make a difference?. (September 2014) - Wiczorek, Rebecca; Manzey, Dietrich; Zirk, Anna
Recent research has shown that the use of 3-stage likelihood alarm systems (LAS) has the potential to mitigate performance deficits associated with the use of binary alarm systems (BAS). The additional likelihood information can guide operators' behavior and improve their decision-making accuracy. Comparisons of LAS with different numbers of stages are missing so far. Therefore, the current study compared a BAS with a 3-stage LAS and a 4-stage LAS. Participants were found to make significantly fewer wrong decisions with the 4-stage LAS than with the other two systems, and still significantly fewer errors with the 3-stage LAS compared to the BAS. We found that this performance benefit resulted from a reduced number of false alarms, whereas no difference was found with regard to misses. Results are further discussed with regard to their theoretical implications for LAS and threshold setting in BAS.